Determinan pajak daerah terhadap pendapatan asli daerah pada kabupaten/kota di Provinsi Sumatera Selatan - Dwidianti, Salsabila; Ardiani, Susi; Fithri, Eka Jumarni (ARKA INSTITUTE, 2022)
The purpose of this study is to prove the effect of Regional Taxes (Motor Vehicle Tax, Motor Vehicle Transfer Fee, and Surface Water Tax) on the Original Regional Income of Regency/City Governments in South Sumatra Province. This study uses a quantitative method with secondary data in the form of the Budget Realization Report of Regency/City Governments in South Sumatra in 2017-2021. The sampling technique uses a purposive sampling technique. The analysis techniques in this study consist of classical assumption tests, multiple linear regression analysis tests, t-tests, F-tests, determination coefficient tests. The instrument used in this study uses the SPSS 26 application. The results of the study show that Motor Vehicle Tax, Motor Vehicle Transfer Fee, and Surface Water Tax have a significant effect on Original Regional Income. It can be concluded that the greater the tax revenue, the greater the Original Regional Income.